7(-x-11)+4=2(x-10)-161

Simple and best practice solution for 7(-x-11)+4=2(x-10)-161 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(-x-11)+4=2(x-10)-161 equation:



7(-x-11)+4=2(x-10)-161
We move all terms to the left:
7(-x-11)+4-(2(x-10)-161)=0
We add all the numbers together, and all the variables
7(-1x-11)-(2(x-10)-161)+4=0
We multiply parentheses
-7x-(2(x-10)-161)-77+4=0
We calculate terms in parentheses: -(2(x-10)-161), so:
2(x-10)-161
We multiply parentheses
2x-20-161
We add all the numbers together, and all the variables
2x-181
Back to the equation:
-(2x-181)
We add all the numbers together, and all the variables
-7x-(2x-181)-73=0
We get rid of parentheses
-7x-2x+181-73=0
We add all the numbers together, and all the variables
-9x+108=0
We move all terms containing x to the left, all other terms to the right
-9x=-108
x=-108/-9
x=+12

See similar equations:

| 2(x-5)+3=9 | | 4(x-5)=2(2x-7)+6 | | 2(x–2)=50 | | Y-(-2)=-(x-4) | | 5y–1=5y+1 | | 7x+30=4x+7=180 | | 9.15=y+5 | | 3(x-4)+2(x+1)=5x-11 | | 4e+24=4X10^24 | | 4+8h=9h−6 | | y=-125+600 | | 3x+14+122.5=180 | | 5-2/3x=1/2x+-4 | | 7=c+37/7 | | -1r=-225 | | 15(2(x-1)=15(2(x+1) | | 24.7=y/12 | | 8x-6=2(x-3)+6 | | 4x−3=2x+7 | | 15u=6u+81 | | 26=12x | | Y-4=x-7 | | 2+a/4=-1+7 | | u÷5=4. | | 5x+32=3x-8 | | 8x+2=-6x-10 | | 7x+15=2(3x+18)+x | | 394z+4)=36 | | -98=4(-6-6r)-2 | | 53.2=19/z | | -5k-2=-7k | | x/3+2x/6=1/3 |

Equations solver categories